2021
DOI: 10.3390/su131910735
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Tensile Behavior of Sustainable Basalt–Carbon, Basalt–Steel, and Basalt–Steel-Wire Hybrid Composite Bars

Abstract: One of the main disadvantages of steel bars is rebar corrosion, especially when they are exposed to aggressive environmental conditions such as marine environments. One of the suggested ways to solve this problem is to use composite bars. However, the use of these bars is ambiguous due to some weaknesses, such as low modulus of elasticity and linear behavior in the tensile tests. In this research, the effect of the hybridization process on mechanical behavior, including tensile strength, elastic modulus, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The concept of the hybridization process refers to applying different materials in one cross-section of an FRP bar to exert a pseudo-ductile behavior on fabricated hybrid FRP bars. As the different materials used for fabricating hybrid FRP bars have a different ultimate tensile strain, this leads to the ductility of fabricated FRP bars under tensile stress [44,101]. Research has shown that the use of steel materials for the fabrication of hybrid composite bars can lead to better ductility, in comparison with fabricating hybrid composite bars by only using different composite materials in one section of each hybrid composite bar.…”
Section: Influence Of Hybridization On Mechanical Properties Of Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of the hybridization process refers to applying different materials in one cross-section of an FRP bar to exert a pseudo-ductile behavior on fabricated hybrid FRP bars. As the different materials used for fabricating hybrid FRP bars have a different ultimate tensile strain, this leads to the ductility of fabricated FRP bars under tensile stress [44,101]. Research has shown that the use of steel materials for the fabrication of hybrid composite bars can lead to better ductility, in comparison with fabricating hybrid composite bars by only using different composite materials in one section of each hybrid composite bar.…”
Section: Influence Of Hybridization On Mechanical Properties Of Compo...mentioning
confidence: 99%
“…Another viable approach to dealing with the aforementioned issues is by using fiberreinforced polymer (FRP) bars. This is due to their appropriate mechanical behavior, such as their tensile strength, durability, and anti-corrosion performance resistance [44][45][46][47][48][49][50][51][52][53][54][55]. Supplanting FRP bars with conventional steel bars can preserve the mechanical behavior of reinforced concrete elements [56].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, mechanical and durability properties of basalt and glass fiber reinforced cement mortars at different fiber lengths and diameters were investigated. Glass [21,22] and basalt [23,24] fibers are among the most widely used fibers in concrete due to their good mechanical and durability properties [25]. Although the production of basalt and glass fibers, both of which are silicate, is similar [26], basalt fibers have a more environmentally friendly production process.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion of embedded reinforcement in reinforced concrete structures is one of the most pervasive global durability challenges [17][18][19][20][21]. The utilization of clay-based SCMs can compromise the durability of concrete materials due to the reduced alkalinity of the pore solution chemistry which is an important factor in arresting chloride-induced electrochemical corrosion of embedded reinforcement [22,23].…”
Section: Introductionmentioning
confidence: 99%